Zjednoczenie Pracy Wsi i Miast w wyborach parlamentarnych 1930 r. - Waingertner, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 2001)
The Labour Union of Villages and Cities (Zjednoczenie Pracy Wsi i Miast - ZPWiM) was a continuation of the Union of the Amendment of the Republic (Związek Naprawy Rzeczypospolitej) - which had been created in 1926 - after the coup d'état of May. It lead the left and the liberal-democratic wing of BBWR (Non-party Block of the Co-operation with the Government - Bezpartyjny Blok Współpracy z Rządem). The bulk of its members was constituted with the radical intelligentsia and a part of the workers’ circles - those who supported Józef Piłsudski and the ideas of syndicalism as well. During the parliamentary electoral campaign 1930 ZPWiM was propagating the slogans of the firm presidency, struggle against the party strife and “seymocracy” (over-influence of the Seym - Polish parliament - on the political system of the stale), interventionism and state control in economy, the need of the organisation of the people within the frame of the firm labour and economic structure, and “the workers-producers class” control over the production. ZPWiM fought sharply against the parties in opposition to the “After May camp” - both on right and left side and those which constituted the so called “Centrolew”, while simultaneously its members were trying to cut off from their “parent party” BBWR. They were afraid of domination of BBWR over ZPWiM, and they noticed the aversion or the leaders of BBWR to the creation of the consequent social-political program capable to unite the people under the banner of “May revolution". During the parliamentary elections of 1930 ZPWiM gained 24 seat in Seym and 4 in Senate. The Members of Parliament from ZPWiM joined the BBWR club in parliament in which they played the role of a kind of an interior opposition contesting conservatism of the leaders of BBWR and the political course leading to the open dictatorship.